2017
DOI: 10.22319/rmcp.v8i4.4255
|View full text |Cite
|
Sign up to set email alerts
|

Eficiencia en el uso del agua de variedades de alfalfa (Medicago sativa L.) con sistema de riego subsuperficial

Abstract: RESUMENSe realizó un estudio con el objetivo de evaluar la eficiencia del agua de riego en la producción de materia seca y proteína cruda en cinco variedades de alfalfa y dos sistemas de riego, en Zacatecas. La siembra se realizó el 2 de febrero del 2012 bajo un diseño de bloques completamente al azar con arreglo de parcelas divididas y tres repeticiones. Los sistemas de riego evaluados fueron goteo sub-superficial (RGS) e inundación en melgas; y las variedades Silverado, Júpiter, 58n57, Excelente, y Gigante. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
1
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 8 publications
1
1
0
Order By: Relevance
“…In the majority of the leguminous the green parts of alfalfa are rich in protein, and its ability to attach atmospheric nitrogen makes alfalfa an important crop for forage production and soil conservation [29]. The results in our study are similar to those obtained in a research study done in Zacatecas by Sánchez [30], who reported in average 20.1 % de PC, in the five varieties used, and below of the results obtained by Urbano [26] in Venezuela who reported a protein content of 22.7 % PC, Chocarro [31] 24 % PC in alfalfa prairies in the winter and [32] who report 25.5 % PC at 30 days cut, similar to the days of cut in our study, however, at 40 days they reported a lower content (18.4 % PC) and in our study during the winter the interval cut was 42 days the protein content was higher. The results found in our study were higher to the ones reported by Zhang [33] who evaluated twenty crops in China and their average results were 18.0 % PC.…”
Section: Protein Content (Pc)supporting
confidence: 87%
“…In the majority of the leguminous the green parts of alfalfa are rich in protein, and its ability to attach atmospheric nitrogen makes alfalfa an important crop for forage production and soil conservation [29]. The results in our study are similar to those obtained in a research study done in Zacatecas by Sánchez [30], who reported in average 20.1 % de PC, in the five varieties used, and below of the results obtained by Urbano [26] in Venezuela who reported a protein content of 22.7 % PC, Chocarro [31] 24 % PC in alfalfa prairies in the winter and [32] who report 25.5 % PC at 30 days cut, similar to the days of cut in our study, however, at 40 days they reported a lower content (18.4 % PC) and in our study during the winter the interval cut was 42 days the protein content was higher. The results found in our study were higher to the ones reported by Zhang [33] who evaluated twenty crops in China and their average results were 18.0 % PC.…”
Section: Protein Content (Pc)supporting
confidence: 87%
“…Agricultural production processes use 75% of available water, so proper use and conservation should be a priority, maintaining a productive and natural balance in hydrographic basins of high environmental interest (Ríos et al, 2016). Because climate change has led to water scarcity, agricultural production has resorted to new production strategies and irrigation management, reducing the amount of water applied without affecting yield, which include the modernization of irrigation systems, intermittent irrigation programs and even the use of new varieties resistant to water stress (Sánchez et al, 2017;Mai et al, 2019).…”
mentioning
confidence: 99%